Experience report supervised stage one on teaching for children - Teixeira, Francisco Claudeci Faustino; Santiago, Ana Paula Mendes; Lima, Jacqueline de Oliveira; Soares, Stela Lopes; Ferreira, Heraldo Simões (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
This scientific work prioritized to describe the healthy practices within the discipline of Supervised Internship One, in Early Childhood Education, that took place in the Dolores Lustosa Educational Center. Having these experiences in the field of action based on the interest in knowing the reality of a certain space that contemplates the professional of Physical Education by law. The objective of this study was to provide a reflection on healthy practices within the Supervised Internship One in Physical Education Degree in early childhood education and to open discussions on the observation, coparticipation and supervised teaching processes carried out during Supervised Internship One, aiming at the integral development of the child. The methodology used in this study was to action research. The qualitative treatment of the findings was chosen as a means of approaching the object of study, through participant observation of two classes of children IV, "B" and "D". During the classes proposed were used recreational activities, appropriate to the age range of children, selected according to a healthy proposal of stimuli to basic motor skills, the interaction needs and participation of the students. At the end of the research it is noticed in the children, an evolution in such aspects as participation, interaction and a significant contribution in the socialization process.